Analysis the Completeness of Integrated Patient Development Records in Diabetes Mellitus Patients - Suraya, Citra; Sansuwito, Tukimin bin; Wisuda, Aris Citra; Rusmarita (Yayasan Rumah Ilmu Professor, 2023)
The Integrated Patient Development Record documents interprofessional collaboration in patient care for health services, especially for patients with chronic problems, including diabetes mellitus. This study aims to determine the completeness of integrated patient progress records in diabetes mellitus patients. This type of research uses a qualitative descriptive method with a sample of 45 people and interviews with five respondents. Based on the research results, 11 forms (24.5%) had data filled in, and 34 forms (75.5%) had incomplete data. The problem factor in filling out integrated patient progress notes lies in verifying the responsible doctor and the results of the service provider's professional instructions. This is due to the large number of patients and limited time. The author provides suggestions for filling out integrated patient progress notes to support accreditation document service standards: a) increase the professional accuracy of service providers in filling out incomplete integrated patient progress notes. b) there needs to be socialization regarding standard operational procedures for integrated patient recording to minimize incomplete forms.